Kesiapan Penggunaan Rekam Medis Elektronik Menggunakan Metode Technology Readiness Index (TRI) di Rumah Sakit Islam Surakarta Yarsis - Az-Zahro, Khumairoh; Andriani, Rika; Pertiwi, Julia (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Indonesian Ministry of Health Regulation Number 24 of 2022 states that all health service facilities was required to implemented Electronic Medical Records no later than December 31 2023. However, the implementation of Electronic Medical Records at the Surakarta Yarsis Islamic Hospital still found unpreparedness in health service facilities both in terms of human resources and software. Measuring readiness to implement a new technology can be done using the Technology Readiness Index (TRI) method. This study aimed to measure readiness to use Electronic Medical Records at RSIS Yarsis. This research was a of descriptive research using a quantitative approach. The research instrument is a closed questionnaire with a Likert scale. The total research population was 293 people, the sample used was 152 people, calculated using the cross sectional formula. Research data was collected by means of interviews and data analysis in research, namely descriptive statistics. The results showed that readiness of Electronic Medical Records using the TRI method obtained a result of 3.28 in the medium technology readiness index category.